2022
DOI: 10.38035/dijefa.v3i3.1323
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Financial Distress and Stock Prices: The Effect of Financial Performance and Sales Growth (Financial Management Review Literature)

Abstract: Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews Stock Price Determination and Financial Distress: Financial Performance Analysis and Sales Growth, A Study of Financial Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
0
0
1
Order By: Relevance
“…Based on signal theory, the higher the sales obtained will give a positive signal to external parties such as creditors because the company can pay its obligations and investors because the injection of funds is successful in the company. The results of this study are consistent with research by Elviana & Ali (2022) and Putri (2021) which revealed that sales growth has an…”
Section: Resultssupporting
confidence: 93%
“…Based on signal theory, the higher the sales obtained will give a positive signal to external parties such as creditors because the company can pay its obligations and investors because the injection of funds is successful in the company. The results of this study are consistent with research by Elviana & Ali (2022) and Putri (2021) which revealed that sales growth has an…”
Section: Resultssupporting
confidence: 93%
“…Shareholders with a high current ratio may bear risk due to the perception that the company is relatively inferior and less capable of generating profits. Research conducted by Zaman (2021), Elviana & Ali (2022) and Ramdany & Manurung (2022) shown a statistically significant and positive correlation between the current ratio and stock price. On the other hand, Ariesa et al (2020) and Prianda et al (2022) elucidate why the current ratio and stock price have a statistically significant negative connection.…”
Section: Current Ratio To Stock Pricementioning
confidence: 91%
“…Financial distress can also be defined as a condition in which a company fails to fulfill its obligations to pay or redeem debts to creditors (Isayas, 2021). Financial distress that occurs in a company will affect investors or creditors who want to invest in the company (Elviana and Ali, 2022) . From the three definitions above, financial distress can be defined as a condition that describes the challenges and difficulties faced by companies in generating sufficient cash inflows to meet obligations to repay debts owned by the company that may affect company's stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%